Conceptualizing the Impact of Special Events on Community Health Service Levels: An Operational Analysis. Issue 5 (4th September 2014) - Lund, Adam; Turris, Sheila A.; Bowles, Ron
Abstract: Mass gatherings (MG) impact their host and surrounding communities and with inadequate planning, may impair baseline emergency health services. Mass gatherings do not occur in a vacuum; they have both consumptive and disruptive effects that extend beyond the event itself. Mass gatherings occur in real geographic locations that include not only the event site, but also the surrounding neighborhoods and communities. In addition, the impact of small, medium, or large special events may be felt for days, or even months, prior to and following the actual events. Current MG reports tend to focus on the events themselves during published event dates and may underestimate the full impact of a given MG on its host community. In order to account for, and mitigate, the full effects of MGs on community health services, researchers would benefit from a common model of community impact. Using an operations lens, two concepts are presented, the "vortex" and the "ripple, " as metaphors and a theoretical model for exploring the broader impact of MGs on host communities. Special events and MGs impact host communities by drawing upon resources (vortex) and by disrupting normal, baseline services (ripple). These effects are felt with diminishing impact as one moves geographically further from the event center, and can be felt before, during, and after the event dates. Well executed medical and safety plans for events with appropriate, comprehensive risk assessments and stakeholder engagement have the best chance of ameliorating the potential negative impact of MGs on communities. A Lund, SA Turris, R Bowles .Conceptualizing the impact of special events on community health service levels: an operational analysis .Prehosp Disaster Med .2014 ;29 (5 ):1 -7 .